Uso de geotecnologias para avaliação da piscicultura na bacia hidrográfica do Rio Iguatemi, no Sul do Mato Grosso do Sul, visando promoção do desenvolvimento sustentável - Klein, Wagner Lopes (2023)
Geotechnologies are a tool used to obtain hydrographic information and soil types, being effective in assisting technical studies of environmental licensing and aquaculture planning. The objective of this work was to use geotechnologies in the evaluation of aquaculture production areas and their contributions in the Iguatemi River sub-basin, in the south of Mato Grosso do Sul. Digital models were used to delimit the sub-basin area elevation (MDE), obtained from data from the National Institute for Space Research, (INPE) and the municipal vectors were obtained from the IBGE website. The nurseries were divided into four classes, I from 300 to 3,000 m², II between 3,001 and 5,000 m², between 5,001 and 10,000 m² and IV greater than 10,001 m². 1651 productive nurseries, stand by nurseries and deactivated nurseries were mapped and classified. Calculations of land use and occupation, altimetry, slope and ordering of river courses were also carried out, in addition to estimates of nitrogen and phosphorus input calculations. The morphometric results indicate an area of 8,222.28 km², exceptionally well drained, with a low risk of large floods. of flood. The nursery classes show that there are 732.78 ha of water depth, with the majority classified as productive nurseries with 513.64 ha of water depth. The estimated inputs of total nitrogen and total phosphorus during breeding were respectively 1,050,573.41 kg and 131,257.01 kg and during harvesting were respectively 41,445.16 kg and 7,235.00 kg. 10 Indigenous Lands were also mapped in 6 municipalities in the sub-basin. Only six municipalities had fish production, and Mundo Novo was the one with the highest production in kg and species. It is concluded that the data obtained in this work shows that the Iguatemi River sub-basin is suitable for fish production.